Regioselective Synthesis of Nanographenes by Photochemical Cyclodehydrochlorination. (22nd December 2015) - Daigle, Maxime; Picard‐Lafond, Audrey; Soligo, Eliane; Morin, Jean‐François
Abstract: Novel nanographenes were prepared by a photochemical cyclodehydrochlorination (CDHC) reaction. Chlorinated precursors were irradiated in acetone in the presence of a base or in pure benzene and underwent multiple (up to four) regioselective cyclization reactions to provide rigid π‐conjugated molecules. Pure compounds were recovered in good yields by simple filtration at the end of the reaction. The CDHC reaction showed compatibility with both electron‐poor and electron‐rich substrates, thus allowing the synthesis of pyridine‐ and thiophene‐fused nanographenes. It also enabled the synthesis of sterically hindered contorted π‐conjugated molecules without causing full aromatization. A kinetic study showed that the CDHC reaction under the conditions used is a very fast process, and some reactions are completed within minutes. The CDHC reaction thus shows great potential as an alternative to other reactions involving harsher conditions for the preparation of nanographenes.